Psychodiagnostics of Preschool children with Autism - Aida Subhan, Nabiyeva (2020)
The article deals with the training and psycho-correction of children with autism. Psychological correction preventing the development of autism plays an important role nowadays. Significant experience has already been gained through clinical and psychiatric studies in this area. Diagnostic criteria for this problem were first identified by Kanner. The article explores the possibilities of determining the characteristics and level of development of purposeful formation of communication skills in preschool children with autism. Based on the obtained indicators, methods that will help to identify and implement more effective methods of pedagogical correction with children with autism individually and in groups are studied as well.